Human Resource Practices in Co-operative Supply and Marketing Federations: A Comparative Study ofMARKFED and HAFED - Kaur, Jasmeet; Dhaliwal, Navkiranjit Kaur (Gyan Management Journal, 2014)
Human Resource Management (HRM) is a strategic and comprehensive approach for managing people and the workplace culture and environment. In order to deveop a sound HRM system, an organization should adopt effective human resource management practices. In the states of Punjab and Haryana, Punjab State Cooperative Supply and Marketing Federation (MARKFED) and Haryana State Cooperative Supply and Marketing Federation (HAFED) are playing important role in building up an integrated structure for remunerative marketing and storing of agricultural produce. The employees are integral part of these co-operative institutions. The present paper attempts to study the human resource practices in the two federations. The study is based on primary sources of the information. Tools like One-Sample Kolmogorov Smirnov test, Reliability Analysis, Average Weighted Scores, Chi-square test, Mann statements regarding overall human resource practices of the fedeation than that of the MARKFED. Further, the majority of the respondents of both the federation agreed that there has been shortage of staff in respective federations. Thus, the two federations should make more effective human resource policy regarding the recruitment, training etc. and continue to take appropriate steps to satisfy and motivate their human resources especially the MARKFED. Whitney Test and Kruska/1-Wallis Test has been used for the analysis of the data. The study found that the employees of the HAFED more strongly agreed with the opinion
Keywords: Human; resource; federations; practices; MARKFED; HAFED